COMPARATIVE MICROBIOLOGICAL ANALYSIS OF WATER STORED IN DIFFERENT STORAGE VESSELS - RADHA.R; SUSHEELA.P (International Journal of Pharma and Bio Sciences, 2015)
Water is most essential for existence of life on earth. Water is the basic necessity of all living creatures and its important use are for drinking purpose. Water intended for human consumption must be safe and free from microbes. Therefore this investigation was taken with the objective to study the effect of storage of lake water in different vessels like plastic, clay, copper and stainless steel by comparing the number of coliforms present in the water before and after storage. The findings may have significant implications in the use of vessels made of copper and its alloys for household storage of drinking water.